Understanding the influence of pullulan on the quality changes, water mobility, structural properties and thermal properties of frozen cooked noodles. (15th December 2021) - Hong, Tingting; Ma, Yue; Yuan, Yirong; Guo, Lunan; Xu, Dan; Wu, Fengfeng; Xu, Xueming
Highlights: Pullulan addition resulted in better texture and minor chrominance differences. Freezable water content and water mobility is decreased in presence of pullulan. Pullulan hampered the depolymerization of gluten during frozen storage. CLSM analysis showed a compact structure in FCN with added pullulan. Abstract: Pullulan is widely applied in the food industry due to its unique physicochemical properties, but little information is known about its effects on the quality of frozen cooked noodles (FCNs), nor the underlying mechanism. In this study, the addition of 0.3% and 0.5% pullulan resulted in better texture and cooking properties, and minor chrominance differences, and it significantly ( P  < 0.05) decreased the freezable water content and retarded the water migration. Pullulan inhibited the depolymerization of the glutenin macropolymer during 0–8 weeks of frozen storage. Meanwhile, pullulan caused slightly decreased α-helixes and increased β-turns, as well as decreased degradation temperature, further suggesting that pullulan influenced the gluten network. A more compact microstructure was shown in the pullulan-fortified FCNs. This study provides a theoretical basis for the positive effects of pullulan on the quality of FCNs from the perspectives of water state and protein structure.